Interaksi Sosial Antar Pedagang Barang Antik di Galeri Industri Kreatif Kota Lama Semarang - Prasetyaningrum, Nurfaizah; Suyanto, Suyanto; Ramadhan, Dani Mohammad (Sabda: Jurnal Kajian Kebudayaan, 2021)
The Creative Industry Gallery (CIG) functions as a space for a diverse range of products from the creative industries, such as fashion, culinary, and furniture, including the uniqueness of antique items offered by the Asem Kawak community. The CIG serves not only as a venue for visitors to engage in transactions but also as a platform for antique traders to interact and conduct their businesses. This research aims to investigate the processes of exchange and transactions among traders, analyzing their interactions. It also seeks to identify key factors contributing to the formation of social networks, including symbolic exchange, values, and practices. Furthermore, this research highlights the contributions of antique traders in fulfilling their family economic needs. To achieve this, the study draws upon Karl Polanyi's concept of social embeddedness, complemented by Frederick Barth's social exchange theory. The chosen research approach is qualitative-ethnographic, involving the collection of information through direct observation, in-depth interviews, and document analysis. Subsequently, the obtained data is carefully examined through reduction, presentation, and drawing research conclusions. Research findings indicate the complexity of social interactions in the formation and maintenance of the Asem Kawak community network. Economic transactions influence social dynamics and individuals' self-perceptions within the group. Social interactions play a key role in collective success. The integration of the antique goods market is based on the concept of reciprocity. Aligned with the embeddedness concept in Polanyi's theory, the success of traders in creating employment opportunities and stimulating economic growth also supports the idea that the economy is closely linked to social and societal factors.